Analysis Of Indonesian Rubber Export Competitiveness - Daulika, Putri; Ridzky Zul Asdi (International Journal of Economics, Business and Innovation Research, 2025)
Rubber is one of Indonesia's leading plantation commodities that is oriented to the international market with export destination countries to several countries. Rubber provides a positive contribution to the economy because it generates foreign exchange for the country. This study aims to analyze (1) the position of Indonesia's rubber competitiveness in internasional comparative advantages and (2) the position of Indonesia's rubber competitiveness in international competitive advantages. This study uses time-series data is from 2000 to 2022. The data were analyzed using a revealed comparative advantage (RCA), and Trade Specialization Index approach (TSI) to know the position competitiveness of Indonesian natural rubber. The results of this study show (1) Based on competitiveness analysis, through Revealed Comparative Advantage (RCA) indicate that the competitiveness of Indonesia's natural rubber exports on the international market has a comparative advantage seen from 2000-2022 with an average value of RCA> 1 which is equal to 1.01. While the competitive advantage for the competitiveness of Indonesian rubber exports is at the maturation stage. This condition occurs because the value of the Trade Specialization Index (TSI) approaches 1, which is 0.98